Assessing System Development Risks. Issue 1 (13th September 2016) - David, Matthew
Abstract: System development projects can fail for lots of different reasons. Those reasons may or may not have been predicted as risks during the development lifecycle. If they weren't predicted, then it is likely that the project team members lacked the level of competence necessary to deliver a system with that level of difficulty. If they were predicted, then it is likely that there was insufficient corporate governance (or assurance), which let the project continue through its lifecycle carrying too much risk. This paper will explore methods on the practical implications of: ‐ Assessing the level of system development difficulty. ‐ Allocating a team of sufficient competency. ‐ Identifying adequate resources. ‐ Tailoring an appropriate amount of governance.